UCCS Moontain Lions Almost Mars Lunar Base Design - Nast, Lindsey; Kilman, Noble; Park, Paul; Hansen, Dylan; Summers, Ronan; Wilcox, Douglas (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
This work involves the design of a first-generation lunar base camp, ALMOST MARS, or Artemis Lunar Mission Operations & Surface Technology for Modular Aeronautics Research Station. NASA is interested in advancements in technology focused on human health, spacecraft environmental control and life support systems, in-situ resource utilization, and the establishment of a permanent human presence on and around the Moon as part of its Artemis Program. The results of this work address those needs by providing the design for a base to sustain a crew of four astronauts for a 45-day lunar mission. The Moontain Lions team designated five areas of project design work: Operations, Mechanical, Electrical, Bioastronautics, and Programmatics. The chosen location for the base was within the crater walls of Shoemaker, located at the lunar south pole. Once that was decided, the team set to work on designing the necessary surface habitat, airlock interface, and ground support equipment and also developed a plan for deployment of equipment and supplies. In addition, the design is shown to meet the power supply, communication, and human environmental control and life support needs. The lunar base will ensure the crew has a safe habitat while conducting research activities and is designed to be expandable to support a long-term presence on the lunar surface.